What Can Chips Technology Offer for Next Century's Chemistry and Life Sciences? - Andreas Manz (CHIMIA, 1996)
Microfabrication gives access to surfaces of a few micron square, and the volumes of picoliter and femtoliter size. Integration of combinatorial synthesis, analysis speed, and small-volume handling are the main advantages. Examples of experimental results in drug discovery, analytical chemistry, and microbiology exhibit the potential of the chip-microstructure approach.